1992
DOI: 10.1002/lsm.1900120415
|View full text |Cite
|
Sign up to set email alerts
|

Dye‐mediated bactericidal effect of He‐Ne laser irradiation on oral microorganisms

Abstract: Little attention has been given to the bactericidal effect of laser irradiation, particularly using low-power energy lasers. It has been demonstrated that He-Ne laser light has an inhibitory action on dental plaque. The purpose of this study was to investigate the bactericidal effect of He-Ne laser irradiation on cariogenic microorganisms. The bactericidal effect was determined by the formation of a growth-inhibitory zone or by the counting of viable bacterial colonies. Streptococcus sobrinus AHT that is a Gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0
3

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 18 publications
2
31
0
3
Order By: Relevance
“…Clearly, the plaque on the irradiated surface of the tooth was found to occupy a smaller area than that which formed on the unirradiated surface. been studied in our laboratory [1]. Of the various dyes screened, when blue or purple dyes were mainly used together with He-Ne laser irradiation, a killing effect was manifested.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Clearly, the plaque on the irradiated surface of the tooth was found to occupy a smaller area than that which formed on the unirradiated surface. been studied in our laboratory [1]. Of the various dyes screened, when blue or purple dyes were mainly used together with He-Ne laser irradiation, a killing effect was manifested.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported that mutans streptococci, used as a representative of oral bacteria, were briefly killed by He-Ne laser irradiation [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Streptococcus sobrinus is sensitive to LLP under these conditions, while Escherichia coli, a Gram-negative enteric micro-organism, is resistant. 25 The effect on the cariogenic micro-organism S. sobrinus is rapid, with leakage of the bacterial membrane detectable after 2 minutes of laser exposure. The bactericidal action of LLP can be obtained with a range of blue, purple, and green dyes within the phenylmethane family, all of which are strong absorbers at 632 nm.…”
mentioning
confidence: 99%